Socio-Economic and Ecological Impact of Charcoal Production in the Fianarantsoa Region, Madagascar - Razafindrazanakolona A. D. EL Agha; Rakotonirina M.D.L.; Ramanampisoa V.E.; Rabesiaka R.; Damy T. S.; Razafimahefa V.M.; Koto-te-Nyiwa Ngbolua; Robijaona Rahelivololoniaina B.; Muhammad Ridwan (Britain International for Academic Research (BIAR-Publisher), 2023)
Charcoal, the main domestic fuel used in the city of Fianarantsoa, comes mainly from the forests of Fianarantsoa II. The increase in demand for charcoal in Fianarantsoa puts considerable pressure on the natural woody formations of Fianarantsoa II. The implication of charcoal burning in deforestation depends on the intensity of charcoal production and the respect of the forest regeneration phase. This activity is, however, essential for charcoal makers who live from it as producers or as resellers. It generates a significant income for the rural population, and even for the resellers in urban areas, despite its relatively low cost compared to other fuels such as gas, oil, ethanol, and electricity. Most charcoal burners are also farmers, but the charcoal produced is intended to meet the urban energy demand of Fianarantsoa. This study focuses on the socio-economic and environmental impacts of this logging in order to highlight the solutions available to ensure sustainable development through the cases of Amnbondrona, Antanifotsy, and Ankaranosy. Environmental education and sustainable development as well as the proposal of income-generating alternatives and more ecological fuels would allow the restoration of environmental harmony while ensuring socio-economic balance.